Quality and quantity of municipal solid waste in Mashhad - Chelliapan, Shreeshivadasan (RJPBCS, 2014)
The yield of human activities created solid waste which nowadays changed a lot in compared to the past because of various in life style. Municipal solid waste is one of the serious environmentconcerns throughoutthe regions of Mashhad. In Mashhad lots of wasteis produced daily. In this study we collect data from various municipal regions in Mashhad. In this paper quality, average generation rate, physical composition, organicmaterial, inorganic material and chemical analysis in all of municipal regions of Mashhad also were investigated. According to the different area in Mashhad the wastes can be divided into eight groups of organic materials, paper and cardboard, rubber and plastics, wood, glass, metals, construction wastes and others. According to obtained results from this study the amount of MSW generated in regions of Mashhad was 585972420 kg per year, and the average generation rate of MSW was 262.2 kg/capita/year. Results showed that the amount of organic material in the regionsof Mashhad is 67.5 % and the amount of inorganic material is 32.5%.